A Study of the KLR Model for Currency Crisis Forecasting in South Korea - Zhang, Lulu (2011)
This paper examines the ability of the Kaminsky-Lizondo-Reinhart (KLR) (1998) model to predict currency crises in South Korea and to forecast the probability of financial crashes in the near future in that country. The sample period of study is from 1991 to 2011, with 1991-2009 being the in-sample period and 2009-2011 being the out-of-sample one. Having operated the original KLR model and a modified model with three extra indicators, this paper finds that the KLR model is moderately accurate when used for South Korean currency crisis prediction, but the modified model is more accurate. Moreover, the indicators of M2 multiplier, domestic credit, real interest rate on deposits, the ratio of M2 to international reserves, imports and the index of stock prices perform well when predicting currency crises. The unemployment rate, current account balance and foreign debts are also accurate predictors of currency crises in South Korea. Compared with the performance of these individual indicators, the composite index constituted by all the above variables has better predictive power. A further finding of this research is that two vulnerable periods for South Korea between 1991 and 2013 emerge from the empirical results of the KLR model. The first period was from 1996 to 1998, which was accurately predicted by the KLR model. The second period was from 2006 to 2009. Even though a subsequent crisis did not occur in South Korea, it very nearly became a reality. An additional feature is that the economy in South Korea in the 2011-2013 periods appears to be stable.